A new species with pink lamellae of Amanita section Caesareae from China - Mu, Man; Huang, Hong-Yan; Zhang, Wen-Hao; Tang, Li-Ping (Phytotaxa, 2021)
Amanita fense is described and illustrated as a new species from China based on morphological and molecular evidence. This fungus is mainly distributed in the eastern, northeastern and southwestern regions of China, such as Anhui, Liaoning, and Yunnan. It is characterized by medium-sized basidiomata, a buff to cacao brown pileus with long-striate pileus margin, pinkish lamellae, and ellipsoid to elongate inamyloid spores. This is the fifth taxon with pink lamellae within Amanita section Caesareae. We provide a comparison with similar species and a key to those taxa that have pink to pinkish gills in this section.